Making greed work in networks a game-theoretic analysis of switch service disciplines. - Shenker, Scott
This paper discusses congestion control from a game-theoretic perspective. There are two basic premises: (1) users are assumed to be independent and selfish, and (2) central administrative control is exercised only at the network switches. The operating points resulting from selfish user behavior depend crucially on the service disciplines implemented in network switches. This effect is investigated in a simple model consisting of a single exponential server shared by many Poisson sources. We discuss the extent to which one can guarantee, through the choice of switch service disciplines, that these selfish operating points will be efficient and fair. We also discuss to what extent the choice of switch service disciplines can ensure that these selfish operating points are unique and are easily and rapidly accessible by simple self-optimization techniques. We show that no service discipline can guarantee optimal efficiency. As for the other properties, we show that the traditional FIFO service discipline guarantees none of these properties, but that a service discipline called Fair Share guarantees all of them. While the treatment utilizes game-theoretic concepts, no previous knowledge of game theory is assumed.
Keywords: Computer systems organization; Computer communication networks; Network architecture and design; Theory of computation; Analysis of algorithms and problem complexity; Nonnumerical algorithms and problems; Mathematics of computing; Discrete mathematics; Graph theory; Network problems; Algorithms; Management; Performance; Theory